The Correlation Between Post-Procedural Complications and Length of Stay Among Post Primary PCI Patients: A Retrospective Study - Sugiharto, Firman; Trisyani, Yanny; Nuraeni, Aan; Alya, Fania Putri (Universitas Padjadjaran, 2025)
Background: Coronary heart disease (CHD) is a leading cause of morbidity and mortality globally. Primary PCI is an effective intervention, it is not without risks, and complications arising post-procedure can significantly affect both patient outcomes and the length of hospital stay (LOS).Aim: To describe the types and frequency of complications that occur in patients after Primary PCI and to analyze their relationship with the length of stay in the hospital.Design: This study employed a retrospective design, utilizing medical records of patients who underwent Primary PCI at a referral hospital in West Java, Indonesia, from December 2019 to April 2024. The study sample was selected using a convenience sampling method, focusing on patients who had complete medical records. Data analysis was conducted using univariate and bivariate analyses, including Fisher's exact test to assess the relationship between complications and LOS. The dependent variable, LOS, was categorized into three groups: ≤ 3 days, 4-5 days, and ≥ 6 days.Results: The findings showed that 81.8% of patients did not experience any complications post-procedure, while 14.5% experienced hematomas and 3.6% experienced bleeding. The median LOS was 4.00 ± 2.28 days, with 60.9% of patients having an LOS of more than 3 days. Patients who experienced complications, especially hematomas or bleeding, were more likely to have prolonged hospital stays, with 11.8% of them staying for ≥ 6 days.Conclusion: Complications following Primary PCI significantly affect the length of stay in the hospital. The study highlights that patients who experience complications such as hematomas or bleeding tend to have longer hospitalizations. These findings underscore the importance of early detection and timely management of post-procedural complications to reduce LOS and enhance patient outcomes.